IMPLEMENTASI NILAI KEBERAGAMAN KEPADA ANAK USIA DINI DALAM MASYARAKAT MAJEMUK MENGGUNAKAN ALAT PERMAINAN EDUKATIF BERBASIS MAZE BOOK DI TK SANTO THOMAS 2 - Jamaludin Jamaludin; Bella Agustiara; Bintang A.G Naibaho; Citra Alwiyah Purba; Eka Santi Sinamo; Roida Ayu Boangmanalu; Zhal Zha Novianti (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
This article or article aims to develop aspects of cognitive development by implementing the APE maze book that researchers deliberately created for students at Kindergarten Santo Thomas 2 as a strategy to stimulate children's cognitive development. This problem is focused on looking at children's cognitive development in order to approach cognitive problems in Early Childhood with reference to Piaget's theory. The data collected through observation and analyzed qualitatively. The research sample was in Kindergarten B Santo Thomas with two classes and research subjects consisting of 26 students. This study concluded that it is important to develop cognitive aspects of children from an early age in order to achieve maximum achievement standards.